Factors affecting value co-creation through artificial intelligence in tourism: a general literature review - Solakis, Konstantinos; Katsoni, Vicky; Mahmoud, Ali B.; Grigoriou, Nicholas (My University, 2024)
Purpose: This is a general review study aiming to specify the key customer-based factors and technologies that influence the value co-creation (VCC) process through artificial intelligence (AI) and automation in the hospitality and tourism industry. Design/methodology/approach: The study uses a theory-based general literature review approach to explore key customer-based factors and technologies influencing VCC in the tourism industry. By reviewing the relevant literature, the authors conclude a theoretical framework postulating the determinants of VCC in the AI-driven tourism industry. Findings: This paper identifies customers' perceptions, attitudes, trust, social influence, hedonic motivations, anthropomorphism and prior experience as customer-based factors to VCC through the use of AI. Service robots, AI-enabled self-service kiosks, chatbots, metaversal tourism and new reality, machine learning (ML) and natural language processing (NLP) are technologies that influence VCC. Research limitations/implications: The results of this research inform a theoretical framework articulating the human and AI elements for future research set to expand the models predicting VCC in the tourism industry. Originality/value: Few studies have examined consumer-related factors that influence their participation in the VCC process through automation and AI.
Keywords: Automation; Machine learning; Metaversal tourism; Mixed reality; Natural language processing; Virtual reality